Linking Information System Design and Competitive Advantage of a Firm: Google Inc. and Yahoo Inc. Case Studies - Korolkova, Ekaterina (2008)
The research aims to indicate and analyse the link between IS design and competitive advantage in a firm expressed in financial performance. The main premise is that the Internet made clearly observable the role of IS design as a final product, as opposed to the traditionally attributed to it supportive role (Byrd, 2001). In order to access the link the research firstly considers the roots of competitive advantage and its sustainability with a particular focus on the Dynamic Capabilities approach and expands this with an inquiry on IS design. Furthermore, to depict the link the search engines of Google Inc. and Yahoo Inc. are taken as representations of IS designs. The two developed case studies analyse the specificity of IS designs in both instances, their transformation over time, thus addressing the sustainability aspect of competitive advantage, and the underlying internal environments in the companies to provide the explanations for the transformations' directions. The research reveals that although the search engines are related to the same product market, yet they differ significantly as well as performance of the two companies, the nature of the embraced competitive advantage and lying in the heart of it competences. The analysis also suggests that the outcomes of operations and their evolution are highly conditioned to the internal practices, which stand in line with the core competences perspective (Prahalad & Hamel, 1990) and the Dynamic Capabilities approach (Teece et al, 1997 & Winter, 2003)